(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
The new regulatory regime applied to companies providing services and sewerage in the country has failed to get the appropriate levels of efficiency required by the sector, because in the different components of its costs structure incorporates a number of factors that significantly raise their levels, moving the effect of higher fees to the users of these services. The distortions of the different components of the costs structure are generated during its calculations because they involve a number of elements that correspond to structural inefficiencies or factors that do not correspond to the service, situation that does not meet one of the guiding principles of the public services scheme, the economic efficiency that should be developed for this kind of endeavor.